Tailor-made starch-based adhesives chemically modified with NaOH:urea and their applications on a cellulosic substrate - Monroy, Yuliana (2023)
Adhesives formulated with native starches have high viscosity, low solids content, poor bond strength and stability due to the starch retrogradation. To overcome this problem, a strategy is the starch treatment with NaOH solution combined with urea, capable of intercalating in the polymeric chains of starch. The aims of this work were to develop adhesives based on chemically modified cassava starch with different NaOH:urea ratios and to study in depth the effect induced by the addition of different concentrations of alkali and urea in the adhesive capacity of formulations that determine their subsequent application in paper-based packaging. Firmness and consistency of the adhesive increased for the 1:1 ratio while it decreased for the NaOH:urea 2:1 ratio, suggesting that the hydrolysis of polymer chains occurred. Additionally, adhesives prepared with 15 % starch maintaining NaOH:urea ratios of 0.5:1: and 1:1 exhibited the highest stress values. ATR-FTIR studies supported the results obtained. It was possible to obtain formulations with different adhesive properties with applications in paper-based packaging. From the analysis of the studied parameters, the combination of 15 % w/w cassava starch with a ratio of NaOH:urea 1:1 allows obtaining adhesives with adequate consistency and adhesive capacity which remain stable during the adhesive storage.